Developing Speaking Skill of Grade XI Students of SMA Negeri 1 Ampibabo through Problem Solving Method - Andi Hikmah; Konder Manurung; Anjar Kusuma Dewi (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This research aims at proving whether or not teaching speaking skills using problem solving method can develop the students’ speaking skills of Grade XI at SMA Negeri 1 Ampibabo. The research employed a quantitative method with one class pretest-posttest design. The instrument of this research was a test. The populations of this research were the Grade XI students at SMA N 1 Ampibabo. The samples were 38 students of class XI IPA 1. The data of this research were collected by administering pretest and posttest. The results of the data analysis indicate that: the mean pretest score is 58.44, the mean posttest score is 67.13 and the t-counted value is 13.35. The t-critical value with a degree of freedom (df) 37 and significance level at 0.05 was 1.687. Based on the analysis above the alternative hypothesis of this research was accepted, because the t-counted value is greater than the t-table value (13.35>1.687). Thus, teaching speaking skills by using problem-solving method can significantly develop the students’ speaking skills.